Genome-wide association study for morphological, phenological, quality, and yield traits in einkorn (Triticum monococcum L. subsp. monococcum). Issue 11 (23rd August 2021) - Volante, Andrea; Barabaschi, Delfina; Marino, Rosanna; Brandolini, Andrea
Abstract: Einkorn ( Triticum monococcum L. subsp. monococcum, 2 n = 2× = 14, A m A m ) is a diploid wheat whose cultivation was widespread in the Mediterranean and European area till the Bronze Age, before it was replaced by the more productive durum and bread wheats. Although scarcely cultivated nowadays, it has gained renewed interest due to its relevant nutritional properties and as source of genetic diversity for crop breeding. However, the molecular basis of many traits of interest in einkorn remain still unknown. A panel of 160 einkorn landraces, from different parts of the distribution area, was characterized for several phenotypic traits related to morphology, phenology, quality, and yield for 4 years in two locations. An approach based on co-linearity with the A genome of bread wheat, supported also by that with Triticum urartu genome, was exploited to perform association mapping, even without an einkorn anchored genome. The association mapping approach uncovered numerous marker-trait associations; for 37 of these, a physical position was inferred by homology with the bread wheat genome. Moreover, numerous associated regions were also assigned to the available T. monococcum contigs. Among the intervals detected in this work, three overlapped with regions previously described as involved in the same trait, while four other regions were localized in proximity of loci previously described and presumably refer to the same gene/QTL. The remaining associated regions identified in this work could represent a novel and useful starting point for breeding approaches to improve the investigated traits in this neglected species.